Oxford Studies in Experimental Philosophy Volume 4 2021
DOI: 10.1093/oso/9780192856890.003.0006
|View full text |Cite
|
Sign up to set email alerts
|

Empiricism is Natural

Abstract: Few questions are as controversial as the origins of knowledge. Chapter 5 demonstrates that laypeople are systematically biased against innate ideas, and that this bias arises from intuitive Dualism and Essentialism. Specifically, if per Dualism, ideas are immaterial, whereas, if per Essentialism, ideas must be material, then it follows that ideas cannot be innate. Experiments 1–4 suggest that people view epistemic traits (i.e., ideas) as less material (e.g., less localized in the brain, in line with Dualism).… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
35
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(41 citation statements)
references
References 0 publications
6
35
0
Order By: Relevance
“…These results confirm that participants are indeed Empiricist—they selectively deny that knowledge and beliefs are possibly innate 8 , 10 , 72 , 73 . Males, however, are less likely to exhibit this bias than females.…”
Section: Resultssupporting
confidence: 70%
See 4 more Smart Citations
“…These results confirm that participants are indeed Empiricist—they selectively deny that knowledge and beliefs are possibly innate 8 , 10 , 72 , 73 . Males, however, are less likely to exhibit this bias than females.…”
Section: Resultssupporting
confidence: 70%
“…Past research has shown that innateness intuitions are indeed linked to embodiment intuitions. When presented with evidence that a psychological trait is embodied, participants are more likely to consider that trait as innate (compared to when told that the same trait has no known anchoring in the body) 8 , 10 , 72 .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations